Advancing Microchannel Fabrication: Tool-Innovated Die Sink Electrodischarge Machining - M. Shanmuka Srinivas; R. Meenakshi Reddy; Praveen Kumar Balguri; Din Bandhu; Manas Das; Kishore Debnath; Mridusmita Roy Choudhury (Journal of Engineering)
In the current fast-changing technological fields, microchannels are playing a vital role by enhancing the field of thermal transfer efficiency. The research aims to explore innovative approaches within die sink electrodischarge machining (EDM) to enhance microchannel fabrication. In micro-EDM, tool wear and unpredictable process parameter effects often hinder hole quality and productivity enhancement. The study delves into innovative tool designs, electrode materials, and process parameters aimed at enhancing both the efficiency and precision of microchannel creation. Stainless steel has long been celebrated for its exceptional corrosion resistance, durability, and versatility across a myriad of industrial applications. The novel tool design utilizes stainless-steel (Grade 301) blades to fabricate microchannels through die sink EDM on SS301 stainless-steel slabs. An investigation was conducted to explore the attributes of microchannels through the optimization of process parameters in die sink EDM. Control parameters such as sparking current, duty cycle, active pulse duration, and gap voltage were selected and studied to assess their impact on the depth and width of the channels. The comprehensive surface morphology of the machined characteristics was evaluated using scanning electron microscope (SEM) and noncontact interferometer images. This study demonstrates that enhancing the depth of the channel can be achieved by decreasing the duty cycle and active duration of the pulse, while increasing the sparking current and gap voltage. Moreover, reducing the duty cycle, active pulse duration, and gap voltage can diminish the overcut of the channel.